An Error Analysis of Students’ Cover Letter Writing Assignments - Qorinta Shinta; Hetty Catur Ellyawati; Hernofika Laksmi Tatas (Universitas PGRI Semarang, 2023)
The objective of this descriptive study was to analyze students' grammatical errors in writing assignments, in this case writing a cover letter for second-semester Computer Science students at the University of Semarang. The target population included 21 Computer Science students enrolled in a Business English class chosen randomly from a pool of 50 participants. They were asked to write an application letter in English. Then, using the surface approach taxonomy, the researcher examined the students' writing for the following errors: 1. Omission Errors; 2. Addition Errors; 3. Misinformation Errors; and 4. Misordering Errors. The findings of this study show that student errors range from the most common to the least common, with a total of 67 phrases: (1) Omission 38.8%, (2) Misinformation on Sub-Alternating Forms 23.8%, (3) Addition on sub-Simple Addition 22.3%, (4) Misinformation on sub-Alternating Forms 8.9%, (5) Addition to sub double markings 2.9%, (6) Misinformation to sub regularization 2.9%. The errors in the Addition type (sub-regularization) and Misinformation categories do not appear at all (0%). According to the data above, pupils still do not comprehend how to employ basic English grammar structures or ho